A 13C‐Labeled Triarylmethyl Radical as an EPR Spin Probe Highly Sensitive to Molecular Tumbling. (21st July 2020) - Poncelet, Martin; Driesschaert, Benoit
Abstract: A stable triarylmethyl spin probe whose electron paramagnetic resonance (EPR) spectrum is highly sensitive to molecular tumbling is reported. The strong anisotropy of the hyperfine coupling tensor with the central carbon of a 13 C1 ‐labeled triarylmethyl radical enables the measurement of the probe rotational correlation time with applications to measure microviscosity and molecular dynamics. Abstract : Measuring tumbling : A stable 13 C1 ‐labeled triarylmethyl radical, whose EPR spectrum is highly sensitive to molecular tumbling, is presented. Owing to the strong anisotropy of the hyperfine coupling tensor, the probe rotational correlation time can be measured. Applications include determining microviscosity and molecular dynamics.